Total Lymfosit Count (TLC) with CD4 in HIV/AIDS Patients at Kupang - Wuan, Adrianus Ola; Herlinalt Gloria Banunu, Ayorince; Kambuno, Norma Tiku (Jurnal Teknologi Laboratorium, 2019)
Human Immunodeficiency Virus (HIV) is a retrovirus originating from the retroviridae family of the genus lentivirus that infects and damages cells that have a molecule Cluster of Differentiation 4 (CD4), especially T lymphocytes that have receptors with high affinity for HIV. Total lymphocyte count / TLC has been proposed as an alternative guide to CD4 in limited health facilities. This study aims to determine the correlation between Total Lymphocyte Count (TLC) and CD4 in HIV/AIDS patients in the W.Z. Johannes Kupang hospital. The type of this research was observational analytic with a cross-sectional design. The study was conducted on 121 samples of patients who performed CD4 examination and Total Lymphocytic Count (TLC) in the laboratory of W.Z.Johannes Kupang Hospital. The Spearman correlation test shows a significance value of 0,000 with a Spearman correlation value of 0.799. Based on the results of this study it can be concluded that there is a significant correlation between Total Lymphocyte Count and CD4 and shows the direction of positive correlation with a very strong relationship, where the increase in the number of Total Lymphocyte Count is in line with the increase in CD4 counts.